Association of dietary and serum vitamin E with bone mineral density in middle-aged and elderly Chinese adults: a cross-sectional study. Issue 1 (28th October 2015) - Shi, Wen-qi; Liu, Jun; Cao, Yi; Zhu, Ying-ying; Guan, Ke; Chen, Yu-ming
Abstract: Previous studies have suggested that vitamin E (VE) may affect bone health, but the findings have been inconclusive. We examined the relationship between VE status (in both diet and serum) and bone mineral density (BMD) among Chinese adults. This community-based study included 3203 adults (2178 women and 1025 men) aged 40–75 years from Guangzhou, People's Republic of China. General and dietary intake information were collected using structured questionnaire interviews. The serum α -tocopherol (TF) level was quantified by reversed-phase HPLC. The BMD of the whole body, the lumbar spine and left hip sites (total, neck, trochanter, intertrochanter and Ward's triangle) were measured using dual-energy X-ray absorptiometry. In women, the dietary intake of VE was significantly and positively associated with BMD at the lumbar spine, total hip, intertrochanter and femur neck sites after adjusting for covariates ( P trend : 0·001–0·017). Women in quartile 3 of VE intake typically had the highest BMD; the covariate-adjusted mean BMD were 2·5, 3·06, 3·41 and 3·54 % higher, respectively, in quartile 3 ( v . 1) at the four above-mentioned sites. Similar positive associations were observed between cholesterol-adjusted serum α -TF levels and BMD at each of the studied bone sites ( P trend : 0·001–0·022). The covariate-adjusted mean BMD were 1·24–4·83 % greater in quartile 4 ( v . 1) in women. However, no significant associations were seen between the VE levels (dietary or serum) and the BMD at any site in men. In conclusion, greater consumption and higher serum levels of VE are associated with greater BMD in Chinese women but not in Chinese men.